2021
DOI: 10.3390/infrastructures6060084
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Recycled Aggregates on the Mechanical Properties of Synthetic Fibers-Reinforced Masonry Mortars

Abstract: The construction sector is one of the main consumers of raw materials and generates a high volume of waste within the European Union. The search for new materials that are more sustainable and respectful of the environment has become a challenge for countries with a high degree of industrialization. In this work, a study of the most relevant properties of masonry mortars made with recycled aggregates and reinforced with synthetic fibers was carried out. Three types of aggregates were used—natural, concrete rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 42 publications
(43 reference statements)
3
5
0
Order By: Relevance
“…This value has an impact on the final properties of mortars and concretes elaborated with these recycled aggregates, since, although it can improve the workability of the mix in a fresh state, it impacts negatively the compressive strength of the hardened sample and causes the decrease in its elasticity modulus [ 48 ]. These effects have been verified in other previous investigations, where it has been observed that mortars fabricated with aggregates that had a higher coefficient of friability impacts negatively compressive strength and elasticity [ 49 ].…”
Section: Analysis Of Resultssupporting
confidence: 84%
“…This value has an impact on the final properties of mortars and concretes elaborated with these recycled aggregates, since, although it can improve the workability of the mix in a fresh state, it impacts negatively the compressive strength of the hardened sample and causes the decrease in its elasticity modulus [ 48 ]. These effects have been verified in other previous investigations, where it has been observed that mortars fabricated with aggregates that had a higher coefficient of friability impacts negatively compressive strength and elasticity [ 49 ].…”
Section: Analysis Of Resultssupporting
confidence: 84%
“…As can be seen in Table 7 and Figure 5, the reference mortars without additions were the ones with the highest mechanical resistance to compression (3.2367 MPa), because they presented a more compact matrix and there were no preferred breakage points, as they did not incorporate insulation materials. For this property, it is observed that the addition of mineral wool fibers did not imply an improvement in compressive strength, as has been observed in other previous studies of fiber-reinforced mortars [77]. Even so, mortars with the addition of mineral wool insulation present higher resistance than mortars with the incorporation of expanded polystyrene granules.…”
Section: Compressive Strengthsupporting
confidence: 74%
“…Water is the essential component responsible for hydrating the cement and providing the mixture with good workability [61]. For this work, drinking water from the Canal de Isabel II of the Community of Madrid was used, which has the following main characteristics [62]: soft hardness (25 mg CaCO 3 /l), neutral pH between 7 and 8 recommended to avoid setting alterations and excessive decreases in strength and durability [63], and a chloride content ranging between 1 and 1.5 mg/L without exceeding the recommended limit for the preparation of mortars [64].…”
Section: Water and Additivementioning
confidence: 99%